Respuesta :

Answer:

x = 14

y = 22

Step-by-step explanation:

y = x + 8

4x - 2y = -12

Solve

_____________

Since we see that the first equation has y alone, we can substitute it into the values of y in the second equation.

4x - 2(x + 8) = -12

Distribute :

4x - (2(x) + 2(8)) = -12

4x - 2x +16 = -12

Combine like terms :

2x + 16 = -12

Subtract 16 from both sides :

2x = -28

Divide 2 from both sides to get x alone :

x = 14

Now that we know what x is, substitute it in the first equation to get y :

y = (14) + 8

y = 22

llibby

Answer:

(2 , 10) or x = 2 & y = 10

Step-by-step explanation:

y = x + 8

4x – 2y = -12​

1. Substitute x + 8 in for the y in the other equation.

2. Solve for x

3. Take the solution for x and substitute the number in for the x in y = x + 8.

4. Solve for y.

5. Your answer is the result.

4x - 2(x + 8) = -12                       Distributive Property

4x - 2x - 16 = -12                        Combine like terms

2x - 16 = -12                               Isolate the x, so start by moving -16

    + 16   +16                              

2x + 0 = 4                                  Delete the 0. It is a place holder you don't need

      2x = 4                                 Isolate the x by dividing both terms by 2.

        2    2

        x = 2

y = x + 8                      Substitute the 2 in for x and solve the one step equation.

y = 2 + 8

y = 10